Analysis and modeling methods of measuring the change of speed of a person’s psychological reaction on movable objects for the use in the development of arcade-like game - O.I. Grabar; A.V. Morozov (Технічна інженерія, 2020)
The methods of sensorimotor reaction, method of reaction of choice, method of reaction of distinction, Shtenberg’s method and method of «mental rotation» for determination of the most effective use in software were considered outages during researches. On the basis of this analysis a programmatic interface is worked out for arcade-like game. The changes of speed reaction of a user on movable objects and possibility of their correlation were analysed. The modeling changes of speed of psychological of a user gives an opportunity to use this software product for the improvement of studies, training of sportsmen.